2014
DOI: 10.1074/jbc.m113.545301
|View full text |Cite
|
Sign up to set email alerts
|

The 2-Oxoacid Dehydrogenase Complexes in Mitochondria Can Produce Superoxide/Hydrogen Peroxide at Much Higher Rates Than Complex I

Abstract: Background: At the redox potential of NADH/NAD ϩ , at least four mitochondrial sites produce superoxide/H 2 O 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
286
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 273 publications
(296 citation statements)
references
References 85 publications
8
286
2
Order By: Relevance
“…Mitochondria can produce superoxide or H 2 O 2 from at least 10 different sites (16,23). Which sites are the major producers in vivo is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mitochondria can produce superoxide or H 2 O 2 from at least 10 different sites (16,23). Which sites are the major producers in vivo is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The sites can be distinguished and studied in situ by providing electrons from appropriate substrates and using specific electron transport inhibitors to isolate them pharmacologically. In this way, at least 10 distinct sites have been characterized in rat skeletal muscle mitochondria (16). These sites are represented as red circles in Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The observation of a similar radical on E1o-ec (18) raised the possibility that such a radical also exists on the E1o-h. There have been several reports that mammalian OGDHc could be a major source of the reactive oxygen species (ROS), superoxide radical anion and hydrogen peroxide, in isolated brain and skeletal muscle mitochondria (5,19) and in the isolated synaptosomes (6), as was also confirmed with the isolated mammalian OGDHc (5,6). Based on experiments with spin-trapping techniques and using the isolated mammalian OGDHc with a modified flavin cofactor of E3, it was concluded that E3-bound FAD is responsible for the production of radical species by OGDHc (20).…”
mentioning
confidence: 99%